The state-of-play in physician health systems leadership research: A review of paradoxes in evidence. Issue 4 (26th September 2019) - Onyura, Betty; Crann, Sara; Freeman, Risa; Whittaker, Mary-Kay; Tannenbaum, David
Abstract : Purpose: This paper aims to review a decade of evidence on physician participation in health system leadership with the view to better understand the current state of scholarship on physician leadership activity in health systems. This includes examining the available evidence on both physicians' experiences of health systems leadership (HSL) and the impact of physician leadership on health system reform. Design/methodology/approach: A state-of-the-art review of studies (between 2007 and 2017); 51 papers were identified, analyzed thematically and synthesized narratively. Findings: Six main themes were identified in the literature as follows: (De)motivation for leadership, leadership readiness and career development, work demands and rewards, identity matters: acceptance of self (and other) as leader, leadership processes and relationships across health systems and leadership in relation to health system outcomes. There were seemingly contradictory findings across some studies, pointing to the influence of regional and cultural contextual variation on leadership practices as well entrenched paradoxical tensions in health system organizations. Research limitations/implications: Future research should examine the influence of varying structural and psychological empowerment on physician leadership practices. Empirical attention to paradoxical tensions (e.g. between empowerment and control) in HSL is needed, with specific attention to questions on how such tensions influence leaders' decision-making about system reform. Originality/value: This review provides a broad synthesis of diverse papers about physician participation in health system leadership. Thus, it offers a comprehensive empirical synthesis of contemporary concerns and identifies important avenues for future research.